Performance and carcass characteristics of broiler chickens with different growth potential and submitted to heat stress - Rosa, P. S. [UNESP]; Faria Filho, D. E.; Dahlke, F.; Vieira, B. S. [UNESP]; Macari, Marcos [UNESP]; Furlan, R. L. [UNESP] (Facta-fundacio Arnco Ciência Tecnologia Avicolas, 2007)
In order to evaluate the effects of broiler genotype and of heat exposure on performance, carcass characteristics, and protein and fat accretion, six hundred one-day-old male broilers were randomly assigned in a 2 x 3 factorial arrangement, according to the following factors: genetic group (selected and non-selected broilers) and pair-feeding scheme (Ad(32) - reared under heat stress and fed ad libitum; Ad(23) - reared at thermoneutrality and fed ad libitum; Pf(23) - reared at thermoneutrality and pair fed with Ad(32)), with a total of six treatments with four replicates of 25 birds each. Independent of pair-feeding scheme, selected broilers showed better feed conversion, higher carcass yield, and lower abdominal fat deposition rate. However, as compared to non-selected broilers, they reduced more intensively feed intake when heat exposed, which promoted significant breast-yield decrease, and more pronounced changes on carcass chemical composition. These findings allows concluding that, in both genetic groups, both environmental temperature and feed-intake restriction influence abdominal fat deposition rate and other carcass characteristics; however, the impact of heat exposure on broiler performance is more noticeable on the selected line.
Keywords: allometric coefficient; carcass yield; genetic improvement; heat stress